Implementation of the Average Effective Income Tax Rate for PKWT Employees at the Security Outsourcing Company PT TFN - Santika, Fizki; Wirawan (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the application of the Average Effective Rate (TER) in calculating Article 21 Income Tax (PPh) for employees with a Fixed-Term Employment Agreement (PKWT) pattern at the security outsourcing service company PT TFN. The application of TER is compared with the progressive rate of Article 17, especially after the enactment of the Minister of Finance Regulation (PMK) Number 168 of 2023 concerning Guidelines for the Implementation of Tax Withholdings on Income in Connection with Work, Services, or Activities of Individuals. The study uses a qualitative approach with triangulation techniques through in-depth interviews, field observations, and document analysis, including simulations of PPh 21 calculations using the progressive method and TER for PKWT employees for the period January–December 2024 with various dependent statuses (TK/0, K/0, K/1, K/2, K/3). The results show that TER simplifies the calculation and reporting of PPh 21 and increases administrative efficiency by around 40–50 percent compared to the progressive rate. However, from a fiscal perspective, TER tends to result in potential underpayments of around 30–40 percent on annual tax returns, especially for employees with variable incomes and multiple dependents (K/2 and K/3). This finding confirms the trade-off between administrative efficiency and tax fairness and suggests that the principle of vertical fairness has not been fully achieved. The study recommends increasing TER socialization, tax education for PKWT employees, and strengthening the integration of digital tax systems to minimize the risk of underpayments and future tax disputes.